Kontribusi PAD dalam APBD sebagai Indikator Keberhasilan Penyelenggaraan Otonomi Daerah - Faisal A Rani; Mahdi Syahbandir; Eddy Purnama (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: This research aims to explain the percentage of the contribution of Regional Own Revenues to Local Government Budget. In every establishment of new autonomy region, it is assumed that it would make the community prosperous by exploring and using all available resources. Apart from that, this research also aims to describe the steps that have been taken by the governments in improving Regional Own Revenues. The research finds that the realization of the budget in 2006, 2007 and 2008 shows that the percentage of such contribution to local government budget is very little compared to the contribution comes from other sources. As a result, the income of such areas is mostly depended on the budget given by central government through the balancing budget known as the General Allocation Grant. According to the data of the realization of Regional Own Revenues for the Local Government Budget in 2006, 2007 and 2008, there was no district or municipality which the contribution higher than 10%. The average contribution during the years had been 5.04%. Ideally, all local government budget especially the regular budget, should be similar to the Regional Own Revenues. This lack of contribution indicates that such local governments were really strongly depended on central government in terms of regular budget and budget for development through the balancing budget. In other words, it could be said that the local governments that are unable to balance between the regular budget and the Regional Own Revenues do not deceive to be called as autonomy governments.        The Contribution of Regional own Revenues as a Success Indicator of Regional Autonomy’s Implementation